Determinants of maternal knowledge of neonatal danger signs among postnatal mothers visiting neonatal intensive care unit, north Central Ethiopia, 2019: a cross-sectional study - Wubet Alebachew Bayih; Biniam Minuye Birhan; Abebaw Yeshambel; Molla Asfaw (BMC, 2020)
Abstract Background Sick neonates can be early readmitted if and only if their mothers have good knowledge of the key neonatal danger signs at first discharge. Thus, it was aimed to assess the level and determinants of maternal knowledge on these signs at first discharge from NICU. Methods A hospital based cross sectional study design was employed at Debre Tabor General Hospital, South Gondar Zone. A sample of 363 participants was included to the study from September 2018 to February 2019 through systematic selection of every other eligible mother baby pair. Data were collected through face to face interview at time of discharge from NICU. Knowledge score of neonatal danger signs was computed by adding the total number of correct spontaneous responses to 9 key danger signs with a minimum score of 0 and maximum of 9 [0 when a mother named none of the key danger signs and 9 when the mother named all the signs]. Mothers who scored ≥3 points were considered to have good knowledge whereas those scoring less than 3 points had poor knowledge. Results 224(61.70%) mothers had good knowledge of neonatal danger signs at discharge from NICU. Secondary and above level of education [AOR = 4.62], receiving danger sign information during stay at NICU [AOR = 3.64], four and above antenatal visits [AOR = 3.04], well preparedness of birth [AOR = 13.70], institutional delivery [AOR = 6.46] and good knowledge of essential newborn care [AOR = 4.41] were significant factors. Conclusions At discharge time, maternal knowledge of neonatal danger signs wasn't comparable to their exposure of NICU environment. Therefore, danger sign education should be routinely given during maternal stay at NICU. Moreover, existing efforts should be enhanced to improve number of antenatal visits, institutional delivery rate and postnatal services along the continuum of maternal and child health care in South Gondar Zone.